In vivo study of Centella asiatica (L.) Urban as a drug gel for diabetes wounds - Rohmayanti, Rohmayanti; Hapsari, Widarika Santi (MEDISAINS, 2021)
Background: Centella asiatica L. Urban is a tropical plant whose spread is quite broad as Indonesia. One of the ingredients of Centella asiatica L. Urban is asiaticoside which has excellent wound healing abilities. However, research on diabetic wound healing with Centella asiatica L. Urban extract formulation in the form of a gel has not been found. Therefore, it is necessary to look at the healing activity of diabetic wounds using Centella asiatica L. Urban extract in the form of a gel.Objective: This experimental study aims to explore the effect of gel extract derived from the Centella asiatica L. Urban on the length of time for wound healing.Methods: The subjects in this study were eight weeks old Balb-C mice conditioned to hyperglycemia and were divided into five groups. The Centella asiatica L. Urban extract is provided in three concentration levels, with 3%, 5%, and 7%. As a form of negative control, used gel without Centella asiatica L. Urban extract and positive control without gel, only hydrocolloid dressing.Results: Centella asiatica L. Urban at concentrations of 3% (with the value of Sig. > 0.05), 5%, and 7% showed the ability to heal wounds.Conclusions: Centella asiatica L. Urban gel extract with a concentration of 3% had a significant effect on wound healing compared to other preparations.